Caries classification and management in the context of the caries care International (CCI™) consensus: a clinical case study (2019)
The objective of this clinical case study is to illustrate the caries management four-step structured process, leading to personalised interventions specifc for each individual patient’s risks and needs, according to CariesCare International, derived from the International Caries Classifcation and Management System (ICCMS) for clinical practice. An 18-year-old female was diagnosed with higher caries risk at the individual level, and with several caries lesions at different severity stages, some likely active and others likely inactive. A care plan was co-created with the patient and delivered to obtain optimal health outcomes. Several issues pertinent to patient-centred care are discussed, including caries management at the individual and the tooth surface level, the preservation of tooth structure, patient’s caries risk management, and prevention and control of caries lesions. The patient’s perspective is taken into account and the health outcome focus of the system is highlighted.